Developing a Culturally Sensitive Framework for Sexual and Reproductive Health Education: Validating With the Fuzzy Delphi Method - Siti Hazariah, Abdul Hamid; Mohammed Rasheedan, Ellin; Siti Roshaidai, Mohd Arifin; Haliza, Hasan; Sajaratulnisah, Othman; Norhasmah, Mohd Zain; Yati, Afiyanti (SAGE Publication, 2026)
Introduction: The lack of a culturally sensitive sexual and reproductive health (SRH) framework in Malaysia has contributed to misguided approaches and low acceptance of sexual education programs. Methods: This study employed the Fuzzy Delphi Method (FDM) to develop and validate criteria for a culturally sensitive SRH framework. Data were derived from interviews with 31 parents and an analysis of an existing parenting sexuality module. Results: Of the 36 proposed criteria, 34 were accepted by the expert panel and categorized into four dimensions. Criterion A6 (SRH provider should encourage those who have strayed to seek repentance) and Criterion C1 (Emphasizing men as the focal point for SRH education) were excluded due to exceeding the threshold value (d > 0.2). Discussion: The FDM analysis prioritized culturally relevant criteria that shape SRH communication, providing guidance for educators and policymakers to strengthen SRH programs in Malaysia.